Efektivitas Mediasi dalam Penyelesaian Sengketa Perceraian di Pengadilan Agama: Analisis Prosedural dan Substansial - Moh. Fauzy S. Sumarto; Musleh Harry (Kartika: Jurnal Studi Keislaman, 2025)
Mediation is a mandatory stage in divorce proceedings within the Religious Courts of Indonesia, as regulated by Supreme Court Regulation (PERMA) No. 1 of 2016. Despite this legal mandate, its effectiveness remains a debated issue in both procedural and substantive aspects. This study aims to examine the effectiveness of mediation through two primary dimensions: procedural effectiveness and substantive effectiveness. Employing a qualitative approach based on normative analysis and literature review, the research reveals that procedural effectiveness is achieved when all mediation stages—such as the appointment of a qualified mediator, the attendance of parties, the conduct of joint and caucus sessions, and the preparation of official reports—are implemented in accordance with legal guidelines. Substantive effectiveness, on the other hand, is reflected in the achievement of fair agreements, balanced communication between parties, the protection of children's interests, and the reduction of post-litigation conflict. The findings emphasize that mediation effectiveness depends not only on whether an agreement is reached but also on the quality of the dialogue and the fairness of the outcome. Strengthening mediator competence, improving mediation facilities, and increasing public awareness are essential measures to enhance the role of mediation in resolving divorce disputes